2010
DOI: 10.1016/j.chemphys.2010.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Force statistics and correlations in dense granular packings

Abstract: In dense, static, polydisperse granular media under isotropic pressure, the probability density and the correlations of particle-wall contact forces are studied.Furthermore, the probability density functions of the populations of pressures measured with different sized circular pressure cells is examined. The questions answered are: (i) What is the number of contacts that has to be considered so that the measured pressure lies within a certain error margin from its expectation value? (ii) What is the statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…figure 1 below), quantitative characterizations of them have only recently been reported. These recent approaches have focused on topological characterizations [3], 2-point correlations in the local hydrostatic pressure [4], and statistics of spatially averaged forces [5]. These works showed that there are some characteristics in the spatial structure of the stress field which are independent of density, but they left open the important question of whether one can define a characteristic lengthscale associated with the general visual impression one gets when observing the contact force network.…”
mentioning
confidence: 99%
“…figure 1 below), quantitative characterizations of them have only recently been reported. These recent approaches have focused on topological characterizations [3], 2-point correlations in the local hydrostatic pressure [4], and statistics of spatially averaged forces [5]. These works showed that there are some characteristics in the spatial structure of the stress field which are independent of density, but they left open the important question of whether one can define a characteristic lengthscale associated with the general visual impression one gets when observing the contact force network.…”
mentioning
confidence: 99%
“…For different size ratios, we found different scaling prefactors of the average and maximum overlaps confirming their different behaviors and thus indicating different shapes of the overlap probability distribution functions [25].…”
Section: Discussionmentioning
confidence: 87%
“…The ratios A m (ρ)/B δ (ρ) are not constant (see Table 1), which means that the probability distribution functions of the overlap are not self-similar, but change shape with increasing ρ [25]. …”
Section: Critical Scalingmentioning
confidence: 99%
“…Since the exponents β, α 1 and α 2 are known, the two scaling laws given by Eqs. (33) and (35) can be evaluated to obtain z 1 and z 2 . When we substitute the numerical values for β = 1/2, α 1 = 1 and α 2 = −2 we obtain that z 1 = 0 and z 2 = −1.…”
Section: Numerical Results and Scaling Propertiesmentioning
confidence: 99%